CHANGING DESIGN STUDIO TEACHING: AN ACTION RESEARCH STUDY OF TEACHER’S AND STUDENTS’ EXPERIENCES - Kazybayeva, Zauresh (Graduate School of Education, 2017)
This action research thesis presents an account of how features of constructivist learning theory were used in a Design studio at one department of architecture in Astana, the capital of Kazakhstan. Constructivism as a paradigm for teaching and learning replaced the behaviourist perspective is widely used in conventional design studio teaching where investigation was carried out. Therefore, this study is a possible answer to the question of how to teach architectural design in a different way rather than in the post-Soviet Kazakhstan fashion where teacher-centred instruction with power relationship prevails. The study has revealed the positive outcomes and challenges of creating a constructivist learning environment in a Design studio. Through various learning activities the link between the classroom environment and students' engagement was identified. According to findings, teacher- student interaction and socio-emotional aspects of learning process influence on students' commitment to learning and on overall learning experience. The course artefacts demonstrated the effect of problem-solving on creativity of architectural students. Moreover, based on the students' current views on the Design studio pedagogy, several issues of the existing cultural context were identified during the study. In addition, action research strategy was examined as a tool for teacher learning and used with the aim to improve my teaching. Consequently, this study contributes to the growth of literature on the capacity of applying action research and self-study to teacher’s professional development in Kazakhstani higher education institutions.
Keywords: Type of access: Restricted; architectural education; design studio; constructivist learning environment; teacher learning; action research